2013
DOI: 10.1016/j.jcrs.2013.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes and patient satisfaction in 9366 eyes using a refractive segmented multifocal intraocular lens

Abstract: Dr. Schallhorn is a consultant to Abbott Medical Optics, Inc. No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
62
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 28 publications
10
62
2
3
Order By: Relevance
“…The largest published case series of bilateral implantation of the Lentis Mplus LS-312 multifocal IOL by Venter et al 9 found excellent distance and near visual acuity in patients after placement of the near segment inferiorly as per the manufacturer's instructions. Incidental rotation of the IOL away from its intended axis has been found to be well tolerated, 9,17 spurring interest in the possibility of deliberate rotation of the near add segment into other positions to gain certain clinical refractive advantages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest published case series of bilateral implantation of the Lentis Mplus LS-312 multifocal IOL by Venter et al 9 found excellent distance and near visual acuity in patients after placement of the near segment inferiorly as per the manufacturer's instructions. Incidental rotation of the IOL away from its intended axis has been found to be well tolerated, 9,17 spurring interest in the possibility of deliberate rotation of the near add segment into other positions to gain certain clinical refractive advantages.…”
Section: Discussionmentioning
confidence: 99%
“…Incidental rotation of the IOL away from its intended axis has been found to be well tolerated, 9,17 spurring interest in the possibility of deliberate rotation of the near add segment into other positions to gain certain clinical refractive advantages. One suggestion is to rotate the near add superotemporally to maximize the theoretical beneficial effect of displacing unwanted near segment coma-induced glare without introducing further unwanted photic symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 In addition, this design allows the reduction of the sources of scattering, halos, and glare. 21 Aberrometry is an important clinical tool for objective diagnosis and eye examination. Here, it is shown that the direct application of conventional and commercial wavefront sensors is not appropriate for accurate estimation of the aberrations in patients implanted with the rotationally asymmetric refractive multifocal IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…There have been different multifocal designs, including diffractive bifocal, 1 apodized diffractive, 2 trifocal, refractive, zonal refractive, 1 rotational asymmetric refractive, 3 and accommodating IOLs in which the optic or optics need to move to achieve accommodation. 4 Bifocal diffractive apodized IOLs have a circular pattern on the optic surface, which allows for diffraction of incoming light into two main distinct foci.…”
mentioning
confidence: 99%